2021
DOI: 10.29303/jppipa.v7ispecialissue.1233
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Elektronik Modul Berbasis Problem Based Learning Pada Materi Zat Aditif Dan Zat Adiktif Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa

Abstract: Kemampuan siswa dalam berpikir secara kritis merupakan salah satu dari beberapa tuntutan siswa yang harus dikuasai pada pembelajaran abad 21 ini, seiringan dengan hal tersebut maka para pendidik harus berupaya untuk meningkatkan kualitas belajar sesuai dengan perkembangan pendidikan di dunia. Kemampuan berpikir kritis termasuk salah satu kompetensi utama yang ditekankan pada implementasi kurikulum 2013. Tujuan dari penelitian ini adalah untuk mengetahui karakteristik, kelayakan, dan keefektivan e-modul zat adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…The assessment results of students' critical thinking based on several indicators (Ennis, 1993) are as follows: From all the obtained results, it can be concluded that Interactive Science Ebook Innovation Based on Project-Based Learning (PjBL) is effective in improving students' critical thinking abilities. This is in line with the research conducted by Prabasari (2021), Liana (2022) and Marlina (2022), which states that the use of electronic teaching materials can engage students to be actively involved in learning, thus enhancing their critical thinking abilities after solving interesting problems presented in the electronic teaching materials. Additionally, Rahman (2021) states that the use of electronic teaching materials in learning results in an average indicator of critical thinking abilities falling in the high category.…”
Section: Improving Critical Thinking Using Interactive Science Ebook ...supporting
confidence: 87%
“…The assessment results of students' critical thinking based on several indicators (Ennis, 1993) are as follows: From all the obtained results, it can be concluded that Interactive Science Ebook Innovation Based on Project-Based Learning (PjBL) is effective in improving students' critical thinking abilities. This is in line with the research conducted by Prabasari (2021), Liana (2022) and Marlina (2022), which states that the use of electronic teaching materials can engage students to be actively involved in learning, thus enhancing their critical thinking abilities after solving interesting problems presented in the electronic teaching materials. Additionally, Rahman (2021) states that the use of electronic teaching materials in learning results in an average indicator of critical thinking abilities falling in the high category.…”
Section: Improving Critical Thinking Using Interactive Science Ebook ...supporting
confidence: 87%
“…Alfian et al (2019) said the development of software-based media or software must include maintainability in the form of analyzability and changeability, portability, namely testing in running applications on several types of devices and usability. Based on these assessments, it can be stated that interactive digital teaching modules in terms of language, material and design are feasible to try out (Alfian et al, 2019;Jatmiko et al, 2022;Marlina et al, 2022;Prabasari & Wahyuningsih, 2021).…”
Section: Development Stagementioning
confidence: 99%
“…Electronic science module can be developed by integrating learning approaches and models, such as SETS (Science, Environment, Technology and Society) (Enawaty, 2023;Muniroh et al, 2023;Yani et al, 2022), problem based learning (Adhelacahya et al, 2023), STEM (Science, Technology, Engineering and Mathematics) (Hendri et al, 2021;Indriana & Kamaludin, 2023), and inquiry (Andriani et al, 2021). The implementation of electronic science module can improve students' critical thinking abilities (Liana et al, 2022;Nurmasyitah et al, 2023;Prabasari & Wahyuningsih, 2021), high level thinking abilities (Rusni et al, 2023), and the abilities of 21 st century students (Susilawati et al, 2023). Thus, using the holistic approach or learning model to the development of electronic science module is not only relevant to the development of educational curricula, but also supports the formation of a generation of students who are ready to face the demands of ever-changing times.…”
Section: Student's Perspectivementioning
confidence: 99%